44.8k views
5 votes
If f(x)=(2x+1)/x find f^-1(x)

User Mike Baron
by
4.9k points

2 Answers

4 votes

Final answer:

To find the inverse function, we interchange x and y, solve for y, and express y in terms of x. Hence, f^-1(x) is equal to 1/(x - 2).

Step-by-step explanation:

  1. First, we substitute y for f(x), so the equation becomes y = (2x + 1)/x.
  2. Next, we interchange x and y to obtain x = (2y + 1)/y.
  3. To find the inverse, we solve for y: xy = 2y + 1. Distribute xy to get xy = 2y + 1.
  4. Now, isolate y by subtracting 2y from both sides: xy - 2y = 1.
  5. Factor out y: y(x - 2) = 1.
  6. Divide both sides by (x - 2) to solve for y: y = 1/(x - 2).
  7. Therefore, the inverse function is f^-1(x) = 1/(x - 2).

User Iterniam
by
4.5k points
4 votes

Answer:

f^-1 x = 1 / (x - 2).

Step-by-step explanation:

Let y = (2x + 1)/x

Find x in terms of y:

xy = 2x + 1

xy - 2x = 1

x(y - 2) = 1

x = 1 / (y - 2)

So f^-1 x = 1 / (x - 2).

User Shahab Qureshi
by
5.0k points